Radiological Outcomes and Operative Time following Total Knee Arthroplasty using Accelerometer-based, Portable Navigation versus Conventional Inter-Medullary Alignment Guides. Issue 2 (16th February 2016) - MacDessi, Samuel; Solayar, GN; Thatcher, N; Chen, Darren B
Objectives: Accelerometer-based, portable navigation instrumentation is a new method of achieving desired resection alignments in total knee arthroplasty (TKA). Methods: After randomisation and the application of exclusion criteria, 79 knees were analysed. 42 patients which underwent TKA using conventional intra-medullary (IM) alignment guides were compared to 37 patients with the use of accelerometer-based, portable navigation device (KneeAlign; OrthoAlign Inc, Aliso Viejo, California). Radiographic results were obtained from post-operative computer-tomography following the CT Perth Protocol. Results: In the IM cohort, 81.0% of patients had a coronal alignment within 3° of a neutral mechanical axis (vs 83.8% with KneeAlign, p=0.74), 81.0% had a femoral coronal alignment within 2° of perpendicular to the femoral mechanical axis (vs 89.2% with KneeAlign, p=0.31), and 92.9% had a tibial coronal alignment within 2° of perpendicular to the tibial mechanical axis (vs 81.1% with KneeAlign, p=0.12). Regarding sagittal alignment, the IM cohort had 90.5% of patients with femoral component alignment within 2° of optimum (vs 91.9% with KneeAlign, p=0.83) and 92.9% had a tibial component alignment within 2° of the optimal tibial slope (vs 89.2% with KneeAlign, p=0.57). The mean tourniquet time (from incision to completion of coronal bone resections) in the IM cohort was 16.5± 8.9 minutes vs 22.2 ± 7.6 minutes in the KneeAlign cohort (p<0.003). Conclusion: Accelerometer-based, portable navigation has a statistically similar outcome in alignment following TKA as IM guides. It is noted that using the portable navigation device does prolong surgical time compared to conventional IM surgery and this may be due to the learning curve.